Study of brown coal humic substances hybrid modification on sorption resistance of biodegradable materials - Lebedev, Vladimir Vladimirovich; Miroshnichenko, Denis Viktorovich; Tykhomyrova, Tetyana Sergiivna ("Interdruk" Poland, Warszawa, 2023)
Researching on brown coal humic substances hybrid modification of biodegradable materials based on pol ylactide and coffee waste for their sorption resistance in different liquid mediums are carried out in this work. The objects of study were extrusion polylactide of the Terramac TP-4000 brand, coffee grounds waste with article size limit from 0.5 to 1 mm, dried to moisture content 0,5% and humic substances, which were obtained by extraction of brown coal. The obtained diffusion coefficient values of different liquids are in the range from 0,95 * 10⁻¹⁰ to 6,65 *10⁻¹⁰ m²\sallow us to conclude that the designed brown coal humic substances hybrid modified biodegrada ble materials based on polylactide and coffee waste can be used as a polymer base in terms of their sorption properties for one and multi-use tableware production.
Keywords: humic substances; brown coal; biodegradable; materials; polylactide; coffee waste; sorption resistance